Happiness falls : a novel - Kim, Angie, 1969- (Hogarth, 2023)
"We didn't call the police right away. When Mia's father doesn't come home from a walk in the local nature reserve, she doesn't think much of it. He must've turned off his phone. Or his battery died. Or he probably stopped for an errand-but doing what exactly? Soon more questions arise and it becomes clear to Mia and her family that he is missing. Or is he?"--